The urgency of developing augmented reality-based biology learning media on genetic substance material - Azrai, Eka Putri; Dewahrani, Yulilina Retno; Suryanda, Ade; Rini, Daniar Setyo; Hamam, Zaky (JPBIO (Jurnal Pendidikan Biologi), 2024)
The implementation of biology learning in the field encounters numerous challenges. Specifically on genetic substance material, students experience learning difficulties due to abstract, interdisciplinary concepts and difficulties in understanding textbooks. This problem can be overcome one way by using learning media. Under current learning demands, technology-based media is appropriate to use. Augmented Reality (AR) based media is one option. The accessibility of augmented reality-based media remains limited, especially for genetic substance material, despite the necessity for media capable of visualizing its complex and abstract characteristics. The results of the needs analysis for teachers and students also show that AR-based media is needed in genetic substance learning. The use of AR media is very possible because of the support of adequate infrastructure. Teachers and students also expressed their willingness to use AR media in learning. Based on the research results, it can be concluded that AR-based biology learning media on Genetic Substance material is urgent to be developed. This media will be able to enrich the variety of biology learning media and become one of the solutions to overcome problems in biology learning, especially genetic substance material.